Optimal Protection Coordination and Sizing of Fault Current Limiter in Radial Distribution System with Distributed Generation - Dhakal, Amrit; Rana, Lalit Bikram; Karki, Menaka (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.